EMBEDDING PANCASILA STUDENT PROFILE VALUES IN AN EFL TEXTBOOK UNDER INDONESIA’S KURIKULUM MERDEKA: A CONTENT ANALYSIS OF TASKS AND ASSESSMENTS - Syafaruddin Marpaung; Nuzwaty Nuzwaty; Burhanuddin Arafah (Jurnal Suluh Pendidikan, 2026)
This study investigates how Pancasila Student Profile (PPP) values are integrated into an advanced English as a Foreign Language (EFL) textbook developed under Indonesia’s Kurikulum Merdeka. Focusing on texts, tasks, and assessments, the study examines how character values are not only represented but also operationalized through instructional design. Using a qualitative content analysis approach informed by educational psychology, the analysis maps the distribution and enactment of six PPP dimensions across instructional components.The findings indicate that critical reasoning, global diversity, and mutual cooperation are most prominently embedded, particularly through discussion texts, collaborative activities, and argument-based tasks. In contrast, faith and noble character and independence appear more frequently as thematic messages than as structured competencies supported by explicit task design or assessment criteria. The results further reveal partial misalignment between value intentions and instructional accountability, as only a limited subset of values is consistently assessed.These findings contribute to international discussions on cultural and character integration in EFL curricula by demonstrating that value internalization depends less on thematic visibility and more on how tasks and assessments activate psychological processes such as reflection, perspective-taking, collaboration, and evidence-based judgment. The study offers a framework for evaluating character integration in language textbooks and provides practical implications for curriculum designers, textbook developers, and teachers working in value-oriented EFL contexts.